Asymmetry and the cytoskeleton: Mechanisms of asymmetric neural stem cell division in Drosophila melanogaster. - Cabernard, C. (Current Topics in Developmental Biology, 2026)
Asymmetric cell division is an evolutionarily conserved mechanism to create cellular diversity. Stem cells utilize this division mode to recreate the stem cell while forming differentiating sibling cells at the same time. Fly neural stem cells, also called neuroblasts, are an ideal system to investigate the mechanisms and functions of asymmetric cell division under physiological conditions. Neuroblasts are intrinsically polarized, containing a molecularly defined apical and basal cell cortex. The proteins associated with the basal cell membrane segregate into a smaller, differentiating ganglion mother cell, which turns off neural stem cell genes and induces differentiation genes. The precise spatiotemporal regulation of the actomyosin and microtubule cytoskeleton are instrumental in neuroblast polarization, spindle orientation and division orientation, cell size asymmetry, and cell fate segregation. This chapter will provide an overview of cytoskeletal dynamics and the underlying regulatory mechanisms during neural stem cell divisions in the developing Drosophila nervous system.